Global state and potential scope of investments in watershed services for large cities. Issue 1 (December 2018) - Romulo, Chelsie; Posner, Stephen; Cousins, Stella; Hoyle Fair, Jenn; Bennett, Drew; Huber-Stearns, Heidi; Richards, Ryan; McDonald, Robert
Abstract Investments in watershed services (IWS) programs, in which downstream water users pay upstream watershed service suppliers for actions that protect drinking water, are increasing in number and scope. IWS programs represent over 170 million of investment in over 4.3 million ha of watersheds, providing water to over 230 million people. It is not yet fully clear what factors contribute to the establishment and sustainability of IWS. We conducted a representative global analysis of 416 of the world's largest cities, including 59 (14%) with IWS programs. Using random forest ensemble learning methods, we evaluated the relative importance of social and ecological factors as predictors of IWS presence. IWS programs are more likely present in source watersheds with more agricultural land and less protected area than otherwise similar watersheds. Our results suggest potential to expand IWS as a strategy for drinking water protection and also contribute to decisions regarding suitable program locations. Investment in watershed services programs is growing, however the factors that contribute to sustainability of such programs are unclear. Here the authors use a large database of cities around the world to show that payment schemes are more likely to be present in watersheds with more agricultural land and less protected areas.